The Effect of Early Mobilization on Increasing Fulfillment of Daily Activities in Post-Operative Patients with Lower Extremity Fractures at Grandmed Hospital - Arfah May Syara; Putri Diana Lumban Tobing (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Fracture is a condition that causes continuous disruption to the bone or cartilage. Injuries occur in the bones, such as the upper and lower extremities, as well as the hip joints to the feet. Early mobilization is useful to help patients move faster and avoid complications. This activity includes changing positions, sitting, standing, and walking independently. Activity of Daily refers to a person's ability to carry out daily activities in order to meet their needs. A quasi-experimental design with a pretest-posttest approach without control was applied in this research. This design is useful for measuring the level of Activity of Daily before and after early mobilization. The sample was determined using purposive sampling so that a sample of 10 participants was obtained. The mean value increased from 6.10 to 11.60, meaning that there was a significant increase in Activity of Daily after early mobilization. The z value of 7.645 indicates a significant difference in the level of Activity of Daily before and after. The p value of 0.001 indicates that early mobilization can increase the level of Activity of Daily participants. It is expected that health workers can apply early mobilization therapy so that muscle stiffness does not occur.